The effect of profession on burnout in hospital staff. (13th March 2018) - Marques, M M; Alves, E; Queirós, C; Norton, P; Henriques, A
Abstract: Background: A high level of burnout has been described in health professionals. However, literature regarding other hospital employees is scarce. Aims: To assess the prevalence of burnout in different professional groups of hospital staff and how the professional category is associated with levels of burnout. Methods: Employees of a University Hospital in Portugal completed a self-administered online questionnaire in 2014–2015. We used the Portuguese version of the Maslach Burnout Inventory—Human Services Survey and scored three dimensions of burnout (emotional exhaustion, depersonalization, personal accomplishment) as low, average or high. We estimated odds ratios (OR) and 95% confidence intervals (95% CI) by logistic regression, adjusting for age, sex, use of anxiolytic/antidepressant drugs and job satisfaction. Results: There was a 10% response rate; 368 questionnaires were available for analysis. High levels of burnout due to emotional exhaustion were observed in all professional categories. Nurses, administrative staff and technicians more frequently scored higher levels of emotional exhaustion (59%, 50% and 50%, respectively) and lack of personal accomplishment (41%, 52% and 38%, respectively) than physicians and healthcare assistants. Not all professionals scored highly for depersonalization. Emotional exhaustion scores were significantly lower in healthcare assistants than nurses (adjusted OR 0.26, 95% CI 0.10–0.64). Conclusions: Burnout affects all professional categories of hospital staff. Future studies should use larger, more representative samples of hospital staff, perform longitudinal analyses and analyse data on specifics of each professional category and other potential confounders.